Phytophthora palmivora RPA1, a Homolog of Phytophthora infestans RPA190, is Irrelevant to Metalaxyl Resistance in Phytophthora palmivora Causing Root and Stem Rot of Durian in Thailand - Kamonwan Sichai; Patcharin Nianwichai; Nutsuda Taraput; Veeranee Tongsri; Pattavipha Songkumarn (한국균학회지)
Root and stem rot caused by Phytophthora palmivora is one of the most serious diseases affecting durian production in Thailand where metalaxyl, an effective fungicide against oomycetes, has been used extensively for a long period to control this disease. Although field isolates of P. palmivora resistant to metalaxyl exist in Thailand, a molecular basis for P. palmivora has not yet been elucidated regarding metalaxyl resistance. The current study tested whether P. palmivora RPA1 (the DNA-directed RNA polymerase I subunit gene), a homolog gene of RPA190 associated with metalaxyl resistance in some isolates of Phytophthora infestans, had a role in the resistance mechanism toward metalaxyl. In total, 40 durian-derived isolates of P. palmivora were assessed for metalaxyl sensitivity using a mycelial growth inhibition assay. The effective concentrations for 50% mycelial growth inhibition values for all isolates tested were in the range of 0.01-872.88 mg/L. The isolates were clustered into three groups: sensitive (n=23), moderately resistant (n=11), and resistant (n=6) groups. No polymorphism was revealed based on multiple alignment analysis of the amino acid sequences translated from the corresponding DNA sequences in the region of RPA1 of the metalaxyl-sensitive (n=5), moderately resistant (n=2), and resistant isolates (n=6). Furthermore, investigation of the RPA1 expression among these representative isolates (n=3, each group) indicated that RPA1 expression may not be involved in the regulation of P. palmivora resistance to metalaxyl. Based on this line of evidence, there was no detected relationship regarding metalaxyl resistance and P. palmivora RPA1.